Identification of the Role of Mume fructus in Treating Nocturnal Asthma Based on Network Pharmacology and In vitro Investigation - Ling-Ling Tang; Yan-Qiu Xu; Ying Yang; Xian-Hong Sun; Bo-Han Wang; Xiao-Lu Shi; Li Liu (World Journal of Traditional Chinese Medicine)
Objective: Mume fructus is commonly used in traditional Chinese medicine to treat nocturnal asthma symptoms. However, the molecular mechanisms underlying its effects on nocturnal asthma have not yet been established. This study evaluated the therapeutic mechanisms of Mume fructus in treating nocturnal asthma. Materials and Methods: Network pharmacology was used to investigate the chemical composition, critical targets, and potential mechanisms of action of Mume fructus in treating nocturnal asthma. “Mume fructus” and “nocturnal asthma” were used as keywords to search the relevant databases. The 16HBE and RAW264.7 cells were treated with various concentrations of Mume fructus and lipopolysaccharides (LPSs). Data provided included analyses of cell viability detected by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide, cell proliferation and apoptosis detected by 5-ethynyl-2’-deoxyuridine and Hoechst 33342, messenger ribonucleic acid (mRNA) levels obtained by real-time polymerase chain reaction, and protein expression detected by Western blotting. Additionally, immunofluorescence was used to detect nuclear translocation. Results: Network pharmacology analyses were mainly enriched in nuclear factor kappa B (NF-κB), mitogen-activated protein kinase (MAPK) pathway, and interleukin (IL)-6. Mume fructus and LPS had no effect on viability, proliferation, and apoptosis in 16HBE and RAW264.7 cells under certain concentration conditions. Mume fructus counteracted LPS-stimulated mRNA and protein expression of IL-6. In addition, Mume fructus treatment prevented the LPS-induced phosphorylation of NF-κB and MAPK pathways, as well as the nuclear translocation of NF-κB p-p65 in the 16HBE and RAW264.7 cells. Conclusions: Mume fructus can treat nocturnal asthma by regulating the NF-κB and MAPK pathways and counteracting IL-6 expression. These findings provide a scientific basis for the use of Mume fructus in the treatment of nocturnal asthma.